A CLINICAL STUDY OF THE USE OF PYRVINIUM PAMOATE WITH PIPERAZINE (VANPAR®) IN THE TREATMENT OF OXYURIASIS AND ASCARIASIS - M.A. Barzgar; N.M. Mojdehi; F. Amini (Tehran University of Medical Sciences, 1974)
In this study oxyuris and ascaris infections alone or in combination were treated with Vanapar a combination of Pyrvinium Pamoate and Piperazine administered in two successive daily doses. This resulted in a 100% cure rate of oxyuriasis as well as a substantial reduction in ova count for ascaris, amounting to 97% success rate in achieving ova count reduction. Vanapar was highly effective for the management of pinworm and roundworm infections in this study. The drug was well tolerated with only seven patients (8.8%) displaying drug-attributable adverse experiences.